IMMEDIATE AND RESIDUAL EFFECT OF BIOCHAR ON SELECTED SOIL PROPERTIES OF COARSE-TEXTURED-SOIL AND AGRONOMIC PERFORMANCE OF MAIZE - Azuka, Chukwuebuka V.; Ekette, Oluebube A.; Umeugokwe, Chigozie P. (Chilean Journal of Agricultural & Animal Sciences, 2025)
The management of large volumes of abattoir waste generated in Nsukka metropolis has been a serious environmental concern. This study investigated the immediate and residual effects of cow dung biochar on selected properties of coarse-textured soil and agronomic parameters of maize in Nsukka, southeastern Nigeria. The treatments consisted of biochar application rates of 0, 10, 20 and 30 t ha-1, replicated six times in a Completely Randomized Design, with maize (Zea mays) as the test crop. Agronomic data (leaf length, leaf width, plant height, plant girth, number of leaves) were collected throughout the 12-week experimental period. Soil samples were collected and analyzed at the end of the study. Both soil and agronomic data were analyzed statistically using the GENSTAT software. The results showed that biochar-amended plots had a significant effect (P < 0.05) on most of the soil and agronomic properties evaluated. Soil pH, soil organic matter (SOM), total nitrogen (TN), available phosphorus (P), calcium (Ca), leaf length, leaf width, plant height and number of leaves increased with increasing rates of biochar application in both the 2020 and residual planting seasons. In addition, macro-, micro- and total porosity, saturated hydraulic conductivity, magnesium (Mg), hydrogen (H), cation exchange capacity (CEC), and plant girth significantly increased with increasing biochar application rates during the 2020 planting season only. Aluminum (Al3+) was not significant in either planting seasons. Bulk density decreased with increasing biochar rates in both planting seasons. It can be concluded that cow dung biochar improves both soil properties and maize agronomic performance. Further studies are recommended to determine the optimal minimum application rate, with 10 t ha-1 suggested as a potentially effective threshold for improving soil quality and maize productivity.